Peran Unsur Kesalahan dalam Membangun Sistem Pemidanaan yang Adil pada Tindak Pidana Pencucian Uang - Riyanto, Agus; Firmasnyah, Hery (Syntax Corporation, 2026)
This study analyzes the crucial role of the error element (mens rea) as a pillar of fair criminal accountability in the context of Money Laundering Crimes (TPPU) in Indonesia. Through an analysis of court decisions and a normative legal approach, this study aims to understand how men's reinterpretation of the norm contributes to the substantive justice of TPPU criminalization. The results show that the application of mens rea remains a problem in the case of TPPU, marked by inconsistent evidence, expansion of responsibility without strong evidence of intent, and the influence of the doctrine of strict liability. Therefore, this study concludes that strengthening understanding and proofmens reais key to preventing excessive criminalization and ensuring proportionate sanctions. Strategic recommendations include harmonizing regulations and increasing the capacity of law enforcement officials.